Coronavirus Disease 2019 Vaccine Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2 Infection in the United States Before the Delta- and Omicron-Associated Surges: A Retrospective Cohort Study of Repeat Blood Donors . (3rd August 2022) - Grebe, Eduard; Yu, Elaine A; Bravo, Marjorie D; Welte, Alex; Bruhn, Roberta L; Stone, Mars; Green, Valerie; Williamson, Phillip C; Feldstein, Leora R; Jones, Jefferson M; Busch, Michael P; Custer, Brian
Abstract: Background: To inform public health policy, it is critical to monitor coronavirus disease 2019 vaccine effectiveness (VE), including against acquiring infection. Methods: We estimated VE using self-reported vaccination in a retrospective cohort of repeat blood donors who donated during the first half of 2021, and we demonstrated a viable approach for monitoring VE via serological surveillance. Results: Using Poisson regression, we estimated an overall VE of 88.8% (95% confidence interval, 86.2–91.1), adjusted for demographic covariates and variable baseline risk. Conclusions: The time since first reporting vaccination, age, race and/or ethnicity, region, and calendar time were statistically significant predictors of incident infection. Abstract : Vaccine effectiveness against acquiring SARS-CoV-2 infection in US blood donors was 88.8% (95% confidence interval, 86.2%–91.1%) during the period January–June 2021, which demonstrates the feasibility of using antibody testing of blood donors to monitor vaccine effectiveness over time.